Mykhailo Hrushevsky: «Cossacks were ruining Moscow walls ...» - Melnychenko Volodymyr (Borys Grinchenko Kyiv Metropolitan University, 2017)
This article deals with Taras Shevchenko's and Mykhailo Hrushevskyi's perception and evaluation of the unique and little known page of the national and international history - the attack of the Moscow Kremlin by the Cossack army of Hetman Sahaidachnyi in autumn 1618. There are certain pages from the Ukrainian history that are forgotten or not well-known in the civil society that, in fact, require the emphasis in the educational process, the patriotic upbringing of youth, the formation of national pride and even a new genetic matrix of historical memory. They include the assault of the Moscow Kremlin by the Cossack army of Petro Sahaidachny, the Ukrainian hetman, on the Pokrov in 1618, that is four centuries ago. The author reminds of the heroic page with the help of Mykhailo Hrushevsky, a prominent Ukrainian historian and statesman, who took over the attention and respect for it from Taras Shevchenko. Hrushevsky signaled the nation that those were not Shevchenko's works that the history of Ukraine should be studied from, but it is impossible to know it in all its colors and completeness of the national bitterness without Kobzar's poetic words. Shevchenko's understanding of the history of Ukraine, that he had melted to become his poetry, has had a much greater impact on readers than any scientific works do. The findings of the research show that the unique and complicated episode of the Ukrainian-Russian relations and political-leadership biography of Sahaydachny requires further serious study and objective evaluation. Moreover, that was not specifically and profoundly done by either Mykhailo Hrushevsky or Dmytro Yavornytsky who did not analyzeit generally and in details. Certain interesting attempts taken by contemporary historians have not materialized in the original study yet.